Low-Frequency Performance Analysis of Semi-Active Cab’s Hydraulic Mounts of an Off-Road Vibratory Roller - Vanliem Nguyen; Jianrun Zhang; Xiuzhi Yang (Shock and Vibration)
To improve the ride comfort of the off-road vibratory roller, the cab’s hydraulic mounts were analyzed to prevent vibration sources transmitting to the cab. However, the cab’s low-frequency shaking in the vertical direction and the direction of forward motion is still great. This study proposes an optimal fuzzy-PID control method for semi-active cab’s hydraulic mounts based on an off-road vehicle roller dynamic model to analyze the low-frequency performance of semi-active cab’s hydraulic mounts under the different operating conditions. In order to evaluate the ride comfort of the off-road vibratory roller with semi-active cab’s hydraulic mounts, the power spectral density (PSD) and the weighted root mean square (RMS) of acceleration responses of the vertical driver’s seat, cab’s pitch, and roll vibrations in the low-frequency range are chosen as objective functions. Contrastive analysis of low-frequency vibration characteristics of the off-road vibratory roller with passive cab’s hydraulic mounts, semi-active cab’s hydraulic mounts without optimization, and semi-active cab’s hydraulic mounts with optimization is, respectively, carried out. The research results show that the semi-active cab’s hydraulic mounts with optimization have an obvious effect on mitigating the cab shaking and improving the ride comfort in comparison with passive cab’s hydraulic mounts and semi-active cab’s hydraulic mounts without optimization.